Estimating the Benefits of Contractual Completeness - Matvos, Gregor (Review of Financial Studies, 2013)
[I provide a revealed-preference-based framework that uses covenant prices and choices to quantitatively study how covenants generate firm benefits by completing debt contracts. I use a rational-expectations-based panel estimator of covenant prices, which does not require quasi-experimental variation, to circumvent the problem of endogenous covenant choices. I find that firms' surpluses exceed the spread paid on a loan. Leverage and interest-rate covenants produce the largest benefits, lending quantitative credence to several standard theories of covenants. Once covenants are chosen, the benefits from fine-tuning them are small, thus rationalizing "boilerplate" covenants. I conclude by discussing the extensions and limitations of my method.]